2021
DOI: 10.1155/2021/8866311
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Study on the Antimicrobial Properties of Resveratrol as an Alternative Therapy

Abstract: Resveratrol is a polyphenolic antioxidant whose possible health benefits include anticarcinogenic, antiaging, and antimicrobial properties that have gained significant attention. The compound is well accepted by individuals and has been commonly used as a nutraceutical in recent decades. Its widespread usage makes it essential to study as a single agent as well as in combination with traditional prescription antibiotics as regards to antimicrobial properties. Resveratrol demonstrates the action of antimicrobia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 185 publications
(201 reference statements)
0
24
0
1
Order By: Relevance
“…Trans-resveratrol can diminish the production of biofilms and toxins and reduce this bacteria's motility. It also avoids the production of exotoxins (including the staphylococcal enterotoxin A) that can activate the immune response of T lymphocytes, which produce immunoglobulin E, increasing irritation and inflammation, and aggravating the clinical condition [66,73].…”
Section: Discussionmentioning
confidence: 99%
“…Trans-resveratrol can diminish the production of biofilms and toxins and reduce this bacteria's motility. It also avoids the production of exotoxins (including the staphylococcal enterotoxin A) that can activate the immune response of T lymphocytes, which produce immunoglobulin E, increasing irritation and inflammation, and aggravating the clinical condition [66,73].…”
Section: Discussionmentioning
confidence: 99%
“…These results may be attributed to the relative abundance of polyphenols such as isoxanthohumol, resveratrol, and kaempferide [ 51 , 52 ]. These types of compounds have been shown to have the ability to inhibit biofilm formation by downregulating the expression of genes such as rsbU and spa, which are genes responsible for bacterial adhesion, communication, and bacterial protection [ 53 , 54 , 55 ]. The extract that showed more significant inhibition of biofilm formation was RAE at 128 ”g/mL against S. epidermidis .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, resveratrol has been extensively studied for its effects on human pathogens. Many studies have shown the antimicrobial activity of resveratrol against a wide range of bacteria, viruses, and fungi [54]. Interestingly, it was demonstrated that resveratrol is able to inhibit replication of human herpes viruses [55], influenza viruses [56], and Epstein-Barr virus [57,58].…”
Section: Resveratrol As An Antimicrobial Agentmentioning
confidence: 99%